A Comparison of The Effects Of Triangular And Rectangular Lower Passing Exercises On Passing Accuracy In Extracurricular Futsal At SMPN 1 Wado (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to compare the effect of triangular and quadrilateral pattern lower passing training on passing accuracy in extracurricular futsal activities at SMPN 1 Wado. This study used a quasi-experimental method with a pretest-posttest control group design involving 18 students who were divided into two groups by purposive sampling. The instrument used to measure passing accuracy is the passing accuracy test from Dr Norbert Rogalski and Dr Ernst G. Degel. Data analysis used a normality test, homogeneity test, independent t-test and r-square test to find out how much influence triangular and quadrilateral patterns of lower passing training on passing accuracy. The results of this study can conclude that both training patterns can make a significant contribution to improving students' passing accuracy. The triangular pattern of lower passing training gives an influence of 58.7%, while the rectangular pattern gives an influence of 54.8%. Although the difference in influence is not statistically significant, practically the triangular pattern shows a slight advantage in improving passing accuracy.